Implementasi Kurikulum Merdeka di Sekolah: Persiapan Mahasiswa UIN Raden Fatah Palembang sebagai Calon Guru dalam Menghadapi Tantangan Pendidikan - Sari, Indah Permata; Bella, Hanum Salsa; Julinda, Julinda; Ersyliasari, Aulia; Annur, Saiful (MODELING: Jurnal Program Studi PGMI, 2024)
The implementation of the Merdeka Curriculum presents various challenges, both in terms of preparedness and understanding of the curriculum concept itself. Teachers are required to be more innovative and creative in designing and conducting lessons. Thus, the implementation of the Merdeka Curriculum aims to prepare students as prospective teachers to face educational challenges. The research method used is a qualitative approach with a case study method. The data used includes interviews, observations, and documentation. The research results show that the Merdeka Curriculum facilitates education students at UIN Raden Fatah Palembang in optimizing teaching tools.